Insights offered by data-mining when analyzing media space data - Škrjanc, Maja (Informatica (Ljubljana), 2001)
Media space consists from many different factors fighting for the attention of customer population in a certain environment. Common problem in bigger environments (or countries) is that datasets describing complete media space is hard or almost impossible to get since the detailed picture is too complex or to expensive to compose. However, this is not the case in environments, which are smaller, and is therefore easier to collect the data. We have access to the data entirely describing the media of polupation of 2 million people. Because of the language and economy this media space fiunctioning relatively independently from different factors, specially outside the country. The data was collected by Medial Research Institute Mediana. The database consists of 8000 questionnaires, gathered in 1998. The sample and the questionnaires were made by comparable research standards. In this paper we will discuss different type of questios, which might become in a great assistants in unfolding the media groups, audience fluctuation and profound understanding of happenings in media space, as well as for their predictions.
Keywords: analiza podatkov; zajemanje podatkov; communication medium; mediji